Ciliary body cysts associated with glaucoma in a Great Dane - PAPAVASILEIOU, E.; DURIEUX, P. (Journal of the Hellenic Veterinary Medical Society, 2019)
An 8-year-old female Great Dane, was referred to the Ophthalmology Unit of the Centre Hospitalier Vétérinaire (CHV) des Cordeliers, for corneal opacity of the left eye that did not respond to topical treatment, administered by the referring vet. On initial examination, bilateral ciliary body cysts were noticed. Lens subluxation, pseudo-plateau iris and glaucoma were observed on the left eye. The diagnosis was confirmed by applanation tonometry and high resolution ocular ultrasonography. Medical treatment resulted in temporary clinical improvement of the left eye. No signs of glaucoma were observed on the right eye upon the last re-check examination.